2011
DOI: 10.1002/mana.200810283
|View full text |Cite
|
Sign up to set email alerts
|

Lawson homology, morphic cohomology and Chow motives

Abstract: In this paper, the Lawson homology and morphic cohomology are defined on the Chow motives. We also define the rational coefficient Lawson homology and morphic cohomology of the Chow motives of finite quotient projective varieties. As a consequence, we obtain a formula for the Hilbert scheme of points on a smooth complex projective surface. Further discussion concerning generic finite maps is given. As a result, we give examples of self-product of smooth projective curves with nontrivial Griffiths groups by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 22 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…This statement follows from Theorem 1.3 and a result of the authors [11] where we have found smooth algebraic curves C such that L p H 2p .C n / is not finitely generated for 1 Ä p Ä n 2 if n 3.…”
Section: Comparing To Homologymentioning
confidence: 55%
“…This statement follows from Theorem 1.3 and a result of the authors [11] where we have found smooth algebraic curves C such that L p H 2p .C n / is not finitely generated for 1 Ä p Ä n 2 if n 3.…”
Section: Comparing To Homologymentioning
confidence: 55%
“…which at the level of π 0 induces the usual intersection pairing on algebraic cycles modulo algebraic equivalence ( [6]). This intersection product is graded-commutative and associative ([11,Prop.2.4]). There exists a canonical cycle map Φ p,k : L p H k (X) → H k (X) which is compatible with pull back, push forward and intersection product.…”
Section: Lawson Homologymentioning
confidence: 99%
“…Now for two smooth projective varieties X, Y of dimension n, m respectively, denote by Corr d (X, Y ) := CH n+d (X × Y ) the Chow group of algebraic cycles of dimension n + d on X × Y . By [11], each Γ ∈ Corr d (X × Y ) determines a homomorphism of Lawson homology Γ * :…”
Section: Lawson Homologymentioning
confidence: 99%
See 2 more Smart Citations